Elevated urinary urea by high-protein diet could be one of the inducements of bladder disorders. Issue 1 (December 2016) - Liu, Ming; Li, Min; Liu, Jiangfeng; Wang, Hongkai; Zhong, Dandan; Zhou, Hong; Yang, Baoxue
Abstract Background Previous work found that urea accumulation in urothelial cells caused by urea transporter B knockout led to DNA damage and apoptosis that contributed to the carcinogenesis. The purpose of this study is to explore the potential connection between high urinary urea concentration and the bladder disorders. Methods A high protein diet rat model was conducted by feeding with 40 % protein diet. In-silico modeling and algorithm, based on the results of microarray and proteomics from the bladder urothelium, were used for the reconstruction of accurate cellular networks and the identification of novel master regulators in the high-protein diet rat model. Pathway and biological process enrichment analysis were used to characterize predicted targets of candidate mRNAs/proteins. The expression pattern of the most significant master regulators was evaluated by qPCR and immunohistochemistry. Results Based on the analysis of different expressed mRNAs/proteins, 15 significant ones (CRP, MCPT2, MCPT9, EPXH2, SERPING1, SRGN, CDKN1C, CDK6, CCNB1, PCNA, BAX, MAGEB16, SERPINE1, HSPA2, FOS) were highly identified and verified by qPCR and immunohistochemistry. They were involved in immune and inflammatory response, cell cycle arrest, apoptosis and pathways in cancer. These abnormally activated processes caused the bladder interstitial congestion and inflammatory infiltrates under the thinner urothelium, cell desquamation, cytoplasm vacuolization, nucleus swelling and malformation in the high-protein diet group. Conclusions We provided evidences that high urinary urea concentration caused by high-protein diet might be a potential carcinogenic factor in bladder.